The Role of Islamic Investment Ethics in Preventing Fraudulent Investments - Azhar Alam; Sri Herianingrum; Muhamad Nafik Hadi Ryandono; Nur Puji Rohmawati (Perbanas Institute, 2023)
The case of bulging investment is still rife and causes losses for investors. This study aims to determine the role of Islamic investment ethics in preventing investment based on theoretical studies through a literature review and reinforced by the opinions of religious experts, investment experts, and law enforcement staff. This study used a descriptive qualitative approach using primary data from theoretical studies from various literature sources and interviews with ten people, including religious and investment experts. Moreover, The results show that the role of Islamic investment ethics in preventing investments such as staying away from riba, gharar, and maysir, using the principle